ALARA in Pediatric Electrophysiology Laboratory - Harinder R. Singh (Children, 2022)
The effects of radiation on patients and the providers are dose-dependent and cumulative. Pediatric patients are not only more sensitive to radiation but also may undergo more procedures and diagnostic tests throughout their lifetime. As providers, the endeavor is to cause no harm and it behooves us to either eliminate or minimize the radiation exposure to patients without affecting the efficacy and outcomes of the diagnostic or therapeutic modalities. Pediatric electrophysiologists have taken the lead in attempting to minimize the radiation exposure to patients and staff with innovative and advanced techniques. The techniques range from minimizing the exposure to radiation with better understanding and applications of the physics associated with fluoroscopic imaging to using alternative imaging modalities that do not use radiation.